The model theory of the field of reals with a subgroup of the unit circle - Belegradek, O; Zilber, B (2008)
We describe definable sets in the field of reals augmented by a predicate for a finite rank multiplicative group Γ of complex numbers contained in the unit circle . This structure interprets the quotient-space /Γ which, for Γ infinite cyclic, is related to the quantum torus. Every definable set is proved to be a Boolean combination of existentially definable sets. We give a complete set of axioms for the theory of such a structure. © 2008 London Mathematical Society.